A panchromatic hybrid crystal of iodoplumbate nanowires and J-aggregated naphthalene diimides with long-lived charge-separated states1. Issue 13 (7th April 2015) - Liu, Jian-Jun; Guan, Ying-Fang; Jiao, Chen; Lin, Mei-Jin; Huang, Chang-Cang; Dai, Wen-Xin
<x xml:space="preserve">Abstract</x> A panchromatic hybrid crystal of anionic iodoplumbate nanowires and J-aggregated protonated naphthalene diimides has been formed through charge-assisted anion–π and lone pair–π interactions.